O processo de verticalização da cidade de Chapecó/SC: 2010 a 2017 - Grosseli, Carliana (2020)
The verticalization process in the city of Chapecó is quite recent, mainly when compared to Brazil, and its emergence started to be more significant from the 1970s. The urban occupation process began with the implementation of the agribusiness in the city, providing new features and ways of using the land. In parallel to this implementation, the enlargement of the urban land has become necessary due to the large population contingent who has immigrated to the city. Soon, there was the implementation of new subdivisions far from the downtown area that, in its turn, acquires new configuration and uses. New enterprises gain space downtown and, later, in pericentral neighborhoods. Among these enterprises, it is possible to highlight the vertical buildings, which are located in many spots of the city providing a new spatial configuration and new value to the urban land. Our object of study is Chapecó’s verticalization process – from 2010 to 2017. The research was conducted from the data survey provided by the City Hall regarding the buildings approved for construction in that period. The collected data allowed the identification of constructed or in-construction buildings as well as the location of each fieldwork. In addition, it also allowed us to identify the producers of verticalized urban space and their performance during that specific period. It is important to highlight the fact that the verticalization is present in several points of the city, each of them, however, has its own features. For instance, buildings with the largest number of floors are located in the central area, on the other hand, buildings with fewer floors are situated in the neighborhoods. For each location, there are companies that operate in the implementation of the buildings, which defines the features for each enterprise